EFEK EKSTRAK ETANOL RIMPANG TEMUGIRING (Curcuma heyneana val) TERHADAP KADAR TRIGLISERIDA - Widyaningsih, Wahyu (Pharmaciana, 2011)
The study of effect ethanolic extract Curcuma heyneana rhizoma as antihypertrigliseridaexamine of rats after given by dietary of high fat has been carried out.This experiment use 28 white male Wistar grooved rats with weight about 150-200gram body weight, at about 2 -3 months old. They were divided into seven grouprandomly and each group 4 rats. The first group was given by standart treatment ofdietary (BR II) and aquadest, the second group was given by dietary of high fatty andaquadest, the third group was given by CMC Na solution, the fourth was given bygemfibrosil in CMC Na suspension, the fifth group, the sixth group and the seventhwere orally given by of ethanolic extract with dose 10g/kgBW; 20 g/kgBW; and 40g/kgBW. Hyperlipidemia was treated with higth dietary fatty (5 gram fat cows and 10gram egg yolk) at the second period (two weeks). The treatment of ethanolic extractCurcuma heyneana rhizoma was given after hyperlipidemia. The trigliserida contentdetermined with GPO (Glycerol-3-Phosphate Oxidase) test. The trigliserida level inthe serum analyzed on the before treatment, during the treatment and after treatment.The result of the research showed that ethanolic extract Curcuma heyneana rhizoma 2weeks can decrease trigliserida level.